Clinical profile of children with Autism Spectrum Disorder in a developmental clinic in Western Cape - Mudawarima, Louisa; Petersen, Reneva (Department of Paediatrics and Child Health, 2023)
Clinical profile of children with Autism Spectrum Disorder in a developmental clinic in Western Cape Abstract Introduction Autism Spectrum Disorder (ASD) is increasingly being recognised as a significant neurodevelopmental condition in African countries. There is some evidence to suggest that the children who present with ASD in Africa may be diagnosed late and have a more severe clinical picture. The purpose of this study was to describe the clinical profile of children with ASD in the neurodevelopmental clinic at Red Cross War Memorial Children's Hospital in Western Cape Province South Africa. Methods We sampled patients with a previous or new diagnosis who attended our clinic during the period January to July 2017. Consenting participants were administered a questionnaire with sociodemographic and clinical questions, clinical details of medical and developmental diagnosis were extracted from medical records and children. were further assessed using the Autism Diagnostic Observation Schedule version 2 (ADOS-2). Results A total of 32 patients were recruited into the study with 26 out of 32 (81%) being boys. On assessment as part of the study, all participants met DSM 5 criteria for the diagnosis of ASD. Most participants (94%) had not experienced general developmental regression but a substantial proportion (39%) had reported early regression of language milestones. Almost half of participants (48%) had self-injurious behaviour reported, 25% had associated motor difficulty and 10% comorbid epilepsy. More than half of participants (53%) required substantial support in day-to-day activities. Most participants (81%) were administered module 1 of the ADOS-2 reflecting the high proportion of children in the sample who were either preverbal or using only single words. Conclusions Children seen in this clinical sample reflected the more severe end of the autism spectrum with a significant proportion having associated comorbidities such as epilepsy, and motor difficulties. The phenotypic profile on the ADOS 2 in this study correlated well with clinical assessments.